Red Meat and Processed Meat Consumption and Risk of Colorectal Cancer - Ozhiganova N. V., Mustafina S. V. (Interactive science, 2019)
the potential connection between consumption of red meat and development of colorectal cancer has been the subject of scientific discussion for a long time. However, uncertainty persists to this day. Consumption of processed meat and red meat may play a role in colon carcinogenesis, among other risk factors. An analysis of the updated data demonstrates an ever-smaller connection between red meat consumption and colorectal cancer incidence.
Keywords: мясная продукция; питание; колоректальный рак; риск колоректального рака; красное мясо; colorectal cancer; risk of CRC; red meat; processed meat